Open Source: the Case of Channels - Cherevatskyi, D.; Lypnytskyi, D.; Myshanov, A. (Економічний вісник Донбасу, 2023)
In global practice, the Open Source phenomenon is usually associated with software. But in reality, the concept of open source code is much broader. There are even examples of open source beer, etc. The study is devoted to the case study of the sea canals (Panama, Suez) in the context of demonstrating the features characteristic of the Open Source phenomenon. Against the background of the requirements for ensuring sustainable development, the Open Source approach can become decisive in terms of industrial development, infrastructure restructuring, and reduction of the environmental footprint in general. The work was carried out by the method of theoretical research, in particular, using the methods of abstraction, analysis, synthesis, case study.